Cardiomyopathy and kidney function in agalsidase beta-treated female Fabry patients: a pre-treatment vs. post-treatment analysis - Wanner, Christoph; Feldt-Rasmussen, Ulla; Jovanovic, Ana; Linhart, Aleš; Yang, Meng; Ponce, Elvira; Brand, Eva; Germain, Dominique P; Hughes, Derralynn A; Jefferies, John L; Martins, Ana Maria; Nowak, Albina; et al. (ESC heart failure, 2020)
AIMS: Long-term treatment effect studies in large female Fabry patient groups are challenging to design because of phenotype heterogeneity and lack of appropriate comparison groups, and have not been reported. We compared long-term cardiomyopathy and kidney function outcomes after agalsidase beta treatment with preceding treatment-naive outcomes. METHODS AND RESULTS: Self-controlled pretreatment and post-treatment comparison (piecewise mixed linear modelling) included Fabry female patients ≥18 years at treatment initiation who received agalsidase beta (0.9-1.1 mg/kg every other week) for ≥2 years, with ≥2 pretreatment and ≥2 post-treatment outcome measurements during 10-year follow-up. Left ventricular posterior wall thickness (LVPWT)/interventricular septal thickness (IVST) and estimated glomerular filtration rate (eGFR, Chronic Kidney Disease Epidemiology Collaboration creatinine equation) analyses included 42 and 86 patients, respectively, aged 50.0 and 46.3 years at treatment initiation, respectively. LVPWT and IVST increased pretreatment (follow-up 3.5 years) but stabilized during 3.6 years of treatment (LVPWT: n = 38, slope difference [95% confidence interval (CI)] = -0.41 [-0.68, -0.15] mm/year, Ppre-post difference <0.01; IVST: n = 38, slope difference = -0.32 [-0.67, 0.02] mm/year, Ppre-post difference = 0.07). These findings were not modified by renal involvement or antiproteinuric agent use. Compared with the treatment-naive period (follow-up 3.6 years), eGFR decline remained modest and stabilized within normal ranges during 4.1 years of treatment (slope difference, 95% CI: -0.13 [-1.15, 0.89] mL/min/1.73m2 /year, Ppre-post difference = 0.80). CONCLUSIONS: Cardiac hypertrophy, progressing during pretreatment follow-up, appeared to stabilize during sustained agalsidase beta treatment. eGFR decline remained within normal ranges. This suggests that treatment may prevent further Fabry-related progression of cardiomyopathy in female patients and maintain normal kidney function.
Keywords: Fabry Disease; izoenzymy; Fabry disease; alpha-Galactosidase; Enzyme replacement therapy; Cardiomyopathies; Fabryho nemoc; Kidney; Cardiomyopathy; Kidney function; kardiomyopatie; Agalsidase beta; Female patients; lidé; ženské pohlaví; Humans; ledviny; Isoenzymes; enzymová substituční terapie; alfa-galaktosidasa; Female; Enzyme Replacement Therapy